2011
DOI: 10.1002/cne.22670
|View full text |Cite
|
Sign up to set email alerts
|

Inputs to the midbrain dopaminergic complex in the rat, with emphasis on extended amygdala‐recipient sectors

Abstract: The midbrain dopaminergic neuronal groups A8, A9, A10 and A10dc occupy, respectively, the retrorubral field (RRF), substantia nigra compacta (SNc), ventral tegmental area (VTA) and ventrolateral periaqueductal gray (PAGvl). Collectively, these structures give rise to a mixed dopaminergic and non-dopaminergic projection system that essentially permits adaptive behavior. Yet, knowledge is incomplete regarding how the afferents of these structures are organized. While the VTA is known to get numerous afferents fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 158 publications
(230 reference statements)
3
57
1
3
Order By: Relevance
“…For example, FG spread to the midbrain reticular formation just above the VTA could result in the FG-labeled cells that we observed in the mouse ZI. Since the ZI projects to this midbrain reticular formation in rats, but not to the VTA (Zahm et al, 2011), it is possible that our current finding of ZI Nts projections to the VTA of mice results from such an experimental artifact (Zahm et al, 2011). This could account for the apparent ZI Nts afferents to VTA found in our mouse study, and the dearth of them previously reported from rats.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, FG spread to the midbrain reticular formation just above the VTA could result in the FG-labeled cells that we observed in the mouse ZI. Since the ZI projects to this midbrain reticular formation in rats, but not to the VTA (Zahm et al, 2011), it is possible that our current finding of ZI Nts projections to the VTA of mice results from such an experimental artifact (Zahm et al, 2011). This could account for the apparent ZI Nts afferents to VTA found in our mouse study, and the dearth of them previously reported from rats.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, the mouse ZI and LHA contain comparable total numbers of Nts neurons projecting to the VTA (Fig. 4), but more sparse ZI Nts projections to the VTA were observed in rats (Zahm et al, 2011). Intriguingly, a higher density of mouse Nts inputs to the VTA arise from the LHA compared to the ZI, despite equivalent total numbers of afferents observed in each site (Table 2 and Fig.…”
Section: Discussionmentioning
confidence: 93%
“…We previously have referred to them collectively as the ‘ventral mesencephalic dopaminergic complex’ (Zahm et al, 2011b), which herein will be shortened to, ‘midbrain DA complex’. It should be clear that the A8–10 taxonomy refers explicitly to DA neurons, whereas the VTA, SNc, RRF are brainstem structures that also contain locally and distantly projecting neurons that utilize as transmitters, either co-expressed with DA or separately, gamma-aminobutyric acid (GABA), glutamate (GLU), various neuropeptides and possibly as yet unknown compounds.…”
Section: Intrinsic Organization and Connectionsmentioning
confidence: 99%
“…NMDA-Rs within the CeA are also capable of controlling the expression of CPP, and the downstream activation of ERK is required for this effect Li et al 2008Li et al , 2011a. The CeA is an output station to midbrain targets implicated in the aversive state that accompanies opiate withdrawal, including the VTA (Zahm et al 2011) and periaqueductal gray (PAG) (Rizvi et al 1991) (Fig. 1).…”
Section: Amygdala Outputsmentioning
confidence: 99%
“…1) (Zahm et al 2011). Evidence suggests that activity within the CeA and BNST during protracted withdrawal may produce a "stress-like" state that can precipitate relapse (Nakagawa et al 2005b;Harris and Aston-Jones 2007).…”
Section: Amygdala Outputsmentioning
confidence: 99%